Analyzing The Effect of Aspect Ratios on Optimal Parametric Settings Using Taguchi, Taguchi-Pareto, and Taguchi-ABC method: A Case Study in Turning Operations for The Inconel X750 Alloy - Adegoke, Ridwan Majekodunmi; Oke, Sunday Ayoola; Nwankiti, Ugochukwu Sixtus (Universitas Atma Jaya Yogyakarta, 2022)
The aspect-based Taguchi optimization approaches have been newly accepted as important routes to optimizing the turning experimental parameters. Unfortunately, due to its embryonic development, scholars have left unexplained the effects of introducing the aspect ratios on the optimal parametric setting. To correct this deficiency, this article proposes an approach to evaluating the effects of introducing aspect ratios in turning experiments, combined with direct factors, on the optimal parametric settings. To correct this deficiency, the purpose of this article is to highlight that a standard universal evaluation method is absent in optimization analysis using the Taguchi method; it proposes an approach to evaluating the effects of introducing aspect ratios in turning experiments, in combination with direct factors, on the optimal parametric settings. Using A novel method of establishing the influence of introducing aspect ratios on the optimal parametric settings is suggested using literature review, and the examination method may be a solid basis for optimal parametric setting evaluations in future undertakings of turning operational evaluations. The Inconel X750 alloy is considered in turning operations, and experimental data from the literature are used to illustrate the method. This article finds that quantifiable differences in the mean values of optimal parametric settings exist for the turning operation of Inconel X750 alloy. The study's originality is its attention to the aspect ratio analysis regarding the optimal parametric setting in a wide range of values. This article aims to initiate discussions for a universal agreement on how the influence of introducing the aspect ratios in the factor-level combination framework of the Taguchi method may be constituted. The utility of this research effort is to enhance resource distribution planning fog turning zero material.